Use of Metakaolin as Pozzolanic Material and Partial Replacement with Cement in Concrete (M30) - Kaur, A.; Sran, V. P. S. (Asian Review of Mechanical Engineering, 2016)
To achieve sustainability in construction world number of substitutions materials are used. Metakaolin is widely used green pozzolanas. Metakaolin is calcinied clay (koalite). It is obtained from raw material i.e. Kaolin Clay (very fine, white). There is very little emission of carbon dioxide whiles the production of Metakaolin as compared to cement hence it is called as green pozzolanas. The chemical properties of cement were compared with Metakaolin, so that we can replace cement with Metakaolin. In this study partial replacement of cement with Metakaolin at 0%, 3%, 6%, 9% and 12% was done. Mix design was prepared with grade M30 concrete. The compressive strength and split tensile strength of concrete was achieved at 12% addition of Metakaolin. Earlier research also indicate that effect of blended Metakaolin on the properties of cement such as consistency, setting time, soundness remains within the acceptable ranges at different standards. It also solve ecological and environmental problems because cheaper production of Metakaolin and more durable. Therefore this paper provides a scope for more research which is required for green and durable concrete.